Escuadras de la muerte : militares, Falange y terrorismo en la II República - Roberto Muñoz Bolaños (Amnis)
This research analyzes the relationship between certain members of the Spanish Army and the fascist party Falange Española de las Juntas de Ofensiva Nacional Sindicalista (FE de las JONS), within the process of brutalization of politics that, as in other European countries, took place at the interwar period. In this process, two distinct stages were distinguished. The first, corresponding to the year 1934 was marked by the control of the party by the monarchists, both civil and military, who wanted to turn it into a paramilitary organization to serve their own interests. The second began in 1935 and lasted til July 1936. It was defined by the new strategy launched by its leader José Antonio Primo de Rivera, who went on to transform the JONS's faith into a paramilitary force in the service of the Army. Its objective was to obtain a position of political primacy in the New State that will arise after the coup d'état that toppled the Second Republic. This second strategy had a notable success, as FE de las JONS became the most important Spanish political force immediately after the uprising and all along the Francoist period.